2005
DOI: 10.1007/s10549-004-3974-0
|View full text |Cite
|
Sign up to set email alerts
|

A phase II trial of imatinib mesylate monotherapy in patients with metastatic breast cancer

Abstract: Imatinib therapy at doses of 800 mg/day was associated with significant toxicity in patients with heavily pre-treated MBC. Our results do not indicate activity for imatinib monotherapy in these unselected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 18 publications
0
67
0
Order By: Relevance
“…However, in contrast to GIST, for which imatinib has proved to be an efficient tailored therapy, experience with imatinib therapy in breast cancer is limited. A trial conducted by Modi et al (2005) did not establish clinical benefit. However, in that study, no c Kit expression was detected in 8 out of the 11 patients enroled with available tissue.…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to GIST, for which imatinib has proved to be an efficient tailored therapy, experience with imatinib therapy in breast cancer is limited. A trial conducted by Modi et al (2005) did not establish clinical benefit. However, in that study, no c Kit expression was detected in 8 out of the 11 patients enroled with available tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor microenvironment is PDGFR-rich, and activation of PDGFR has been implicated in playing an important role in elevating the IFP (38). High IFP, in turn, could decrease the uptake of chemotherapeutic drugs (41).…”
Section: Discussionmentioning
confidence: 99%
“…15,19,20 As a result, it is not that surprising that multiple clinical trials have observed only minimal or no clinical efficacy of imatinib mesylate (Gleevec) in various types of tumors expressing KIT detected by immunohistochemical staining but lacking activating mutations, such as adenoid cystic carcinomas of the salivary gland, 22 pulmonary small cell carcinomas, 32,33 breast carcinomas, 34 ovarian carcinomas 35 and melanomas. 36 These studies 15,19,20,22,[32][33][34][35][36] support the concept that mutation-mediated activation of KIT or PDGFRA is a prerequisite for successful treatment with imatinib mesylate. 37 This conclusion is further supported by a recent study in which clinical response to imatinib mesylate was observed in a patient with metastatic thymic carcinoma harboring an activating KIT mutation.…”
Section: Discussionmentioning
confidence: 99%